Partisipasi Penyusunan Anggaran dan Sistem Pengendalian Internal terhadap Pencegahan Kecurangan pada Pengelolaan Dana Sekolah - Hari Purnama (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to empirically determine the prevention of fraud in school fund management which is influenced by participation in budget preparation and internal control systems, both partially and simultaneously. This type of research is survey research using data collection techniques with questionnaires. The type of data for this research is primary data, namely data directly obtained from respondents. Population of all principals, teachers, administrative staff and school committees of State High Schools in Bantul Regency. The sample for this research is part of a population of 100 respondents. The technique used in sampling is the purposive sampling method. The data analysis technique used is a linear regression analysis technique with a significance of 5%. The hypothesis tests used are the t test and F test. This research shows the results that both partial and simultaneous participation in budget preparation and the internal control system have a positive and significant effect on preventing fraud in managing school funds.